2018
DOI: 10.1007/s10616-018-0242-4
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin-3-glucoside enhances mitochondrial function and biogenesis in a human hepatocyte cell line

Abstract: Mitochondrial dysfunction has been identified as one of the primary factors contributing to liver diseases. Pathways that control mitochondrial biogenesis are potential therapeutic targets for the amelioration of hepatocyte dysfunction and liver disease. Research on natural pharmacological agents that ameliorate liver diseases has intensified over the last two decades. Cyanidin-3-glucoside (Cy3g), a dietary flavonoid compound extracted from a wide variety of fruits and vegetables, reportedly has several benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The mechanisms through which tart cherries may improve exercise performances seem to be related with their high contents in cyanidin-3-glucoside. This anthocyanin has been demonstrated to enhance mitochondrial biogenesis in both mice [ 134 ] and a human hepatocyte cell line [ 135 ] through upregulating skeletal muscle PGC-1α, leading to an activation of lactate metabolism [ 134 ] and, finally, enhancing the skeletal muscle oxidative capacity and improving the endurance performance in a similar manner as previously suggested for quercetin [ 111 ]. Moreover, the upregulation of PGC-1α induced by the cyanidin-3-glucoside intake increases the expression of vascular endothelial growth factor α (VEGFα), improving the muscle blood supply and oxygen availability and, hence, explaining a potential improvement in exercise performances [ 134 ].…”
Section: Discussionmentioning
confidence: 93%
“…The mechanisms through which tart cherries may improve exercise performances seem to be related with their high contents in cyanidin-3-glucoside. This anthocyanin has been demonstrated to enhance mitochondrial biogenesis in both mice [ 134 ] and a human hepatocyte cell line [ 135 ] through upregulating skeletal muscle PGC-1α, leading to an activation of lactate metabolism [ 134 ] and, finally, enhancing the skeletal muscle oxidative capacity and improving the endurance performance in a similar manner as previously suggested for quercetin [ 111 ]. Moreover, the upregulation of PGC-1α induced by the cyanidin-3-glucoside intake increases the expression of vascular endothelial growth factor α (VEGFα), improving the muscle blood supply and oxygen availability and, hence, explaining a potential improvement in exercise performances [ 134 ].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the expression of NRF1 and TFAM was increased in the presence of Cy3g. The upregulated amounts of the mentioned genes indicate the improvement of mitochondrial function and biogenesis in presence of Cy3g [113].…”
Section: Amla C2c12 Myotubesmentioning
confidence: 99%
“…Many rodent and human studies showed that impairment of hepatic SIRT1 signaling was closely associated with obesity and ALD (33,34). Activated SIRT1 has a regulatory effect on hepatic lipogenesis, fatty acid oxidation, oxidative stress, and inflammatory response Fig.…”
Section: Discussionmentioning
confidence: 99%